Taxonomic complexity in the halophyte Limonium vulgare and related taxa (Plumbaginaceae): insights from analysis of morphological, reproductive and karyological data - Cortinhas, Ana (Ann Bot, 2015)
Background and Aims Limonium is a well-known example of a group of plants that is taxonomically complex due to certain biological characteristics that hamper species' delineation. The closely related polyploid species Limonium vulgare Mill., L. humile Mill. and L. narbonense Mill. are defined species and can be used for studying patterns of morphological and reproductive variation. The first two taxa are usually found in Atlantic Europe and the third in the Mediterranean region, but a number of intermediate morphological forms may be present alongside typical examples of these species. This study attempts to elucidate morphological, floral and karyological diversity representative of these taxa in the Iberian Peninsula. Methods The extent of morphological differentiation was tested through comparison of 197 specimens from both Portugal and Spain using 17 descriptive morphological characters and 19 diagnostic morphometric characters. Analyses of floral morphisms (heterostyly and pollen–stigma dimorphism) and karyological determinations were also conducted. Key Results and Conclusions Discriminant analysis using morphometric variables reliably assigned individuals in natural populations to their respective groups. In addition, the results provide the first direct evidence that L. narbonense and a new species, Limonium maritimum Caperta, Cortinhas, Paes, Guara, Espírito-Santo and Erben, sp. nov., related to L. vulgare are present on Portuguese coasts. Most of these species are found together in mixed populations, especially L. vulgare and L. narbonense. It is hypothesized that taxonomic biodiversity found in sites where distinct species co-occur facilitates the evolutionary processes of hybridization, introgression and apomixis. This study therefore contributes to the elucidation of the taxonomic diversity in L. vulgare-related species and may also help in implementing future conservation programmes to maintain the evolutionary processes generating biodiversity.